RANCANG BANGUN APLIKASI PENJUALAN MAKANAN SEHAT BEDASARKAN PERHITUNGAN KALORI MENGGUNAKAN BMR PADA RUMAH SAKIT ISLAM JEMURSARI - Utama, Dio Putra; Sudarmaningtyas, Pantjawati; Churniawan, Agus Dwi (Jurnal Sistem Informasi Universitas Dinamika, 2020)
Currently, Indonesia needs education about balanced nutrition. Jemursari Islamic Hospital (RSI) Surabaya contribute to educating the community about the requires of calories everyone. The nutrition department, as a part of RSI, controlled directly to dissemination information and healthy provision food. Dissemination information about balanced nutrition and sale of healthy food is conduct in conventional ways, so the information provided is less able to reach the wider community. This study aims to develop application based on Android that has feature the calculation of basal metabolic rate (BMR) using the Harris-Benedict formula. System Development Life Cycle (SDLC) method that consists of four stages implemented in this study.Â The four stages are communication, planning, modelling, and construction. The result of this study achieving the functional rate of 100% based on black-box testing using 60 test cases and white boxes using Junit Android Studio tools. From the result can be concluded that all functions in the application can run appropriately and able to reduce BMR calorie calculation time from 2 minutes 30 seconds becomes 3 seconds.